The impact of L-Arginine supplementation on disorders associated with obesity - Żyga, Justyna (Journal of Education, Health and Sport, 2022)
Introduction: L-Arginine (2-amino-5-guanidinovaleric acid) is a conditionally essential amino acid and a natural constituent of dietary proteins, serving as a precursor for the synthesis not only of proteins, urea, polyamines, proline, glutamate and creatine. This amino acid is a substrate for nitric oxide production, an endogenous messenger molecule involved in a variety of endothelium mediated physiological effects in the vascular system. State of knowledge: The evidence suggests supplementation of L-Arginine may have a positive impact in conditions associated with obesity - type 2 diabetes, atherosclerosis or hypercholesterolaemia. The L-Arginine intake improves insulin sensitivity and may improve lipid profile reducing triglyceride serum levels. As a precursor for nitric oxide synthesis, a molecule involved in a variety of physiological effects in the vascular system, L-Arginine can have a positive impact on the cardiovascular system. Conclusions: The evidence suggests that the L-Arginine may improve lipid profile reducing triglyceride serum levels. L-Arginine could be used as a strategy to improve endothelial function in the selected group of patients. Careful studies are necessary to assess its safety profile, determine under which conditions L-Arginine supplementation is appropriate and when it is undesirable. Attention should be focused to markers of oxidative stress and blood pressure stability.